2019
DOI: 10.1016/j.enconman.2019.01.064
|View full text |Cite
|
Sign up to set email alerts
|

High performance and thermal stress analysis of a segmented annular thermoelectric generator

Abstract: Nomenclature r radius, mm angle of a single thermoelectric leg, degree half of the angle between two legs, degreeHigh performance and thermal stress analysis of a segmented annular thermoelectric generator

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(54 citation statements)
references
References 68 publications
0
44
0
Order By: Relevance
“…In addition, steady state heating is also analysed and compared to the transient pulsed heating. The numerical model used in this study has been verified by the authors in [3], [7] therefore, the results from this study can be trusted as accurate.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, steady state heating is also analysed and compared to the transient pulsed heating. The numerical model used in this study has been verified by the authors in [3], [7] therefore, the results from this study can be trusted as accurate.…”
Section: Resultsmentioning
confidence: 57%
“…Therefore, renewable energy sources are being paid more attention recently due to the unique advantages they offer such as inexhaustibility and low pollution. In automobiles, about 40% of fuel energy is wasted as exhaust gas in the internal combustion engine [3]. Therefore, there is need for a technology that can utilize this waste heat for beneficial use.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated energy conversion efficiency and thermal reliability of segmented flat [18][19][20] and segmented annular. [21][22][23][24][25] Optimization of STEG systems has also been considered. Ma et al 26 investigated different TE segment length ratios to evaluate the performance of flat STEGs and showed that increasing the length of skutterudite segments led to the enhanced TE performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations of annular thermoelectric generators (ATEG) and segmented annular generators (SATEG) show that the performance is optimal when the annular shape parameter , that is, the power increases with the increase of Sr , reaches its maximum value when it becomes a flat-plate thermoelectric and decreases the power again. It has also been shown that to improve the heat transfer capacity and efficiency, the contact area of the high temperature zone ( ) can be increased 14 16 .…”
Section: Introductionmentioning
confidence: 99%